Nutritional intake when cycling under racing and training conditions in professional male cyclists with type 1 diabetes - Pitt, J. P.; Bracksen, R. M.; Scott, S. N.; Fontana, F. Y.; Skroce, K.; McCarthy, O. (Journal of Sports Sciences, 2022)
This study sought to detail and compare the in-ride nutritional practices of a group of professional cyclists with type 1 diabetes (T1D) under training and racing conditions. We observed seven male professional road cyclists with T1D (Age: 28 ± 4 years, HbA_1c: 6.4 ± 0.4% [46 ± 4 mmol.mol^-1], VO_2max: 73.9 ± 4.3 ml.kg ^-1.min^-1) during pre-season training and during a Union Cycliste Internationale multi-stage road cycling race (Tour of Slovenia). In-ride nutritional, interstitial glucose, and performance variables were quantified and compared between the two events. The in-ride energy intake was similar between training and racing conditions (p = 0.909), with carbohydrates being the major source of fuel in both events during exercise at a rate of 41.9 ± 6.8 g.h^-1 and 45.4 ± 15.5 g.h^-1 (p = 0.548), respectively. Protein consumption was higher during training (2.6 ± 0.6 g.h^-1) than race rides (1.9 ± 0.9 g.h^-1; p = 0.051). A similar amount of time was spent within the euglycaemic range (=70-=180 mg.dL^-1): training 77.1 ± 32.8% vs racing 73.4 ± 3.9%; p = 0.818. These data provide new information on the in-ride nutritional intake in professional cyclists with T1D during different stages of the competitive season.